Sweetened beverages, snacks and overweight: findings from the Young Lives Cohort Study in Peru - Bernabe-Ortiz, Antonio (2017)
Proyecto de investigación 2017-2019, financiado por la Universidad Peruana de Ciencias Aplicadas (UPC).